THE FRAGMENTED COMMUNICATION STRUCTURE WITHIN CORRUPTION PRACTICES GENERATED BY ACCOUNTABILITY AND FINANCIAL CONTROL - Ionescu, Luminiţa (Analele Universităţii Spiru Haret. Seria Jurnalism [Annals of Spiru Haret University. Journalism Studies], 2017)
The aim of this paper is to present the impact of financial control and accountability over the corruption practices and the connection between public opinion and control mechanisms. Corruption control is a priority for governments all over the word and anti-corruption policies have become more visible on the political agenda. Implementing financial control and a strong ethical environment will prevent the development of corruption practices. In the last decades, corruption has become one of the most problematic factors of doing business in European Union.
https://katalog.adlr.link/Record/ai-53-556925